Syntax Verbalization of Modern Media Names: Stylistic and Communicative-Pragmatic Aspects - Kostusiak, Nataliia; Shulska, Nataliia; Hromyk, Yurii; Masytska, Tetiana; Prosianyk, Oksana; Sazonova, Yaroslava; Naumenko, Liana; Rozhylo, Mariia (My University, 2023)
The article characterizes the syntactic means of expression of newspaper headlines, in the field of which sentences of different status and structure are presented, their communicative and pragmatic potential and stylistic role are clarified. It is noted that the representation of Ukrainian media names is mainly related to simple two-syllable constructions (53.3%), to a slightly lesser extent – to one-syllable constructions (46.7%). It was found that the two-syllable constructions presented in the heading complexes are usually common and expressively neutral, although sometimes they contain linguistic units that amplify the expression of phase, give it an emotional and evaluative color, which makes the journalistic material attractive to the recipient. Focusing on the modal plan and the frequency of use made it possible to recognize narrative expressions as dominant, and to include interrogatives in the field of peripheral ones. It was determined that a limited expression is inherent in a two- syllabic incomplete sentence. The application of the method of quantitative calculations provided a hierarchy of monosyllabic constructions, among which the unmarked-personal (62.4%), definite-personal (16.3%), impersonal (8.2%), nominative (7.8%), and infinitive (5.3%) syntactic units are fixed. It was found that most of the two-syllable and one-syllable sentences that form the headlines of newspaper articles are uncomplicated. The periphery includes constructions structured by complicating components, in particular, sentences with homogeneous members, addresses, sentences separated by members, and modal syntaxes. The article focuses on headings modeled by complex syntactic units. It has been observed that complex syntactic units are represented in a rather limited way in media names, and in terms of quantitative indicators, there are complex sentences without conjunctions on the opposite axis to them. Complex constructions of non-segmented and segmented structure, aimed at attaching information about the content of the publication, were analyzed.
Keywords: headline; mass media; syntax; syntactic units; sentence; communicative- pragmatic aspect; stylistic role; jargon; secondary nomination; Ukrainian language